2012
DOI: 10.5665/sleep.1974
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Dream Lucidity Obtained from Contrasting Lucid versus Non-Lucid REM Sleep: A Combined EEG/fMRI Case Study

Abstract: In line with recent EEG data, lucid dreaming was associated with a reactivation of areas which are normally deactivated during REM sleep. This pattern of activity can explain the recovery of reflective cognitive capabilities that are the hallmark of lucid dreaming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
180
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(195 citation statements)
references
References 15 publications
10
180
0
5
Order By: Relevance
“…For example, Dresler et al (2012) found an increased activation during REM lucid dreams, not only in the prefrontal, but also in the occipitotemporal cortices, bilateral precuneus, cuneus and parietal lobes. These cerebral areas can also be targeted for stimulating lucid dreaming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Dresler et al (2012) found an increased activation during REM lucid dreams, not only in the prefrontal, but also in the occipitotemporal cortices, bilateral precuneus, cuneus and parietal lobes. These cerebral areas can also be targeted for stimulating lucid dreaming.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study, which has used fMRI to study cerebral regional activation in lucid dreams, replicated these findings and showed that, in lucid dreams, not only prefrontal but also occipito-temporal cortices, bilateral precuneus, cuneus and parietal lobes exhibit higher activation compared to what occurs during non-lucid dreams (Dresler et al, 2012). Based on this background, the hypothesis was formulated that activation of the frontolateral area of the brain during REM sleep should increase the probability of lucid dreaming.…”
Section: Tdcs Effects On Dream Luciditymentioning
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, our study is the first to investigate the relationship between lucidity, metacognition and dream anxiety. Interestingly, the dorsolateral prefrontal cortex has been suggested to be a common brain region for metacognitive processes and LD in functional magnetic resonance imaging studies (1,32).…”
Section: Discussionmentioning
confidence: 99%
“…Dreaming is a state characterized by delusional thought, bizarre or peculiar dream pattern with gaps, deficiencies in judgment and metacognition, and complete lack of insight (1,2). Mota Rolim et al (2) reviewed the studies of Hobson et al (3) and Muzur et al (4) and reported that hypofrontality could reduce self-awareness and induce delusional thoughts and deficiencies in rational judgment, both in REM sleep and in episodes of psychosis.…”
Section: Introductionmentioning
confidence: 99%